Diversity of bats in 2 protected limestone areas in Sarawak - Mohd Ridwan, Abd Rahman; Roberta Chaya, Tawie Tingga; Noor Haliza, Hasan; Sigit, Wiantoro; Anang Setiawan, Achmadi; Eileen, Lit; Besar, Ketol; Huzal Irwan, Husin; Abdullah, M.T (Sarawak Museum, 2010)
The assessment of bats diversity from two limestone forests in protected areas of Sarawak, the Niah National Park (NP) and the Wind Cave Nature Reserve (NR) were conducted from November 2007 until April 2009. The assessments were aimed to update the current diversity of bats as well as to compile their composition with previous studies done at selected limestone areas in Sarawak. Eight to twelve mist nets and three harp traps were used, with accumulated effort of 572 trap-nights for both the Niah NP and the Wind Cave NR. A total of 1,520 individuals representing 36 species from 17 genera and 10 families were recorded. Penthetor lucasi, Hipposideros cervinus and Cynopterus brachyotis were the three most abundant species captured in both sampling areas. Meanwhile, nine species of bats are new for both localities. Seven out of nine are the new additional records added for the Niah NP, namely, Hipposideros ater, H. bicolor, H. cineraceus, Coelops robinsoni, Rhinolophus trifoliatus, Murina rozendali and Kerivoula hardwickii.